Genetic suppressor of fd-gogat1 reveals crosstalk among brassinosteroids, photorespiration, and amino acid metabolism - Klimpel, Katherine A.; Findlay, Annika; Menon, Sannidhi; Cytron-Walker, Leah; Dedow, Caylynn A.; Camou, Lazlo; Cadarso, Michela; McGuire, Meghan F.; Pietroske, Jeff; Idowu, Daniel; Busche, Michael; Brunkard, Jacob O. (Frontiers in Plant Science, 2025)
IntroductionA classical forward genetic screen for Arabidopsis mutants with altered morphology identified a pleiotropic mutant, orbiculata (orb1), that has phenotypes including rounded leaves, chlorosis, and reduced growth. orb1 mapped to one of the Arabidopsis genes that encodes glutamate synthase, fd-gogat1 (ferredoxin-dependent glutamine oxoglutarate aminotransferase or Fd-GOGAT).MethodsTo discover why this glutamate synthase impacts development, we conducted a forward genetic screen for suppressors of orb1. In the primary mutagenized generation, we identified a dominant mutant, which we call Lettuce, that rescues orb1 chlorosis but causes new pleiotropic defects that closely resemble the classical Arabidopsis cabbage and dwarf mutants that are defective in brassinosteroid or gibberellin signaling. Here, we take a chemical genetic approach to phenocopy Lettuce and investigate how gibberellins and brassinosteroids impact the development and physiology of fd-gogat1.ResultsWe found that inhibiting brassinosteroid synthesis significantly increases chlorophyll content in fd-gogat1, which is chlorotic due to defects in the photorespiratory pathway.DiscussionThis discovery highlights how crosstalk among phytohormones (brassinosteroids) and core metabolic processes (amino acid biosynthesis and photorespiration) converge to regulate plant development and physiology.